Implikasi Hifzhul Qur'an Terhadap Kebermaknaan Hidup - Laili Rachmah (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2003)
Along with the advancement of technology, information and the flow of globalization, humans are faced with various existing conflicts, both social, economic, cultural, and so on, resulting in feelings of helplessness, unhappiness, anxiety, depression and loneliness. One of the main motivations for humans is the desire to live a meaningful life, for example working and creating so that their lives feel meaningful and valuable. The elements of meaningful life include a clear life goal, namely happiness in this world and the hereafter. Therefore, the author wants to know the meaningfulness of the life of a Hifzhul Qur'an, in the short and long term.